A Proposed Framework for Network Security Audit Trail for Ministry of Domestic Trade & Consumer Affairs - Fara, Jamal (2006)

(untitled)
The tremendous growth of the Internet, and particularly the World Wide Web (The Web) on 1989, has led to mass usage of networking. Organization regardless of government or private sector depends on their network to run the business. Computer threats such as virus, worms and attack like DDOS, hackers emerge align with the improvement of network. Many organization face problems on their network regardless of Local or Wide area network. Deployment of security equipments to protect the network is useless if the organization cannot track the root of the security problems. This can actually be done by conducting a network security audit. It is the best way to understand the organization security stand and the problem involve with the network. It depends on the organization weather to use the framework design by other researcher or customize their own framework in order to conduct network security audit in the organization.